Knowledge of mothers regarding children's vaccinations in Cyprus: A cross-sectional study - Kyprianidou, Maria; Tzira, Eleana; Galanis, Petros; Giannakou, Konstantinos (My University, 2021)
Introduction Vaccine hesitancy is identified as one of the top threats to global health. A significant drop of childhood vaccine coverage is reported worldwide. One of the key reasons that influenced mothers' choice to postpone, or avoid children's vaccination, is knowledge. This study aimed to assess the level of Cypriot mothers' knowledge on certain aspects of vaccination of their children, examine the association between vaccination knowledge and selected socio-demographic factors, and lastly assess the association of mothers' knowledge about vaccination with vaccination coverage and delay, compliance to the recommended schedules, vaccination during pregnancy and mother-pediatrician relationship. Methods An online-based cross-sectional study conducted to collect information about socio-demographic characteristics, child's characteristics, vaccination, and vaccine knowledge, using a self-administered questionnaire. The survey was conducted between April 2020 and June 2020 and the study population included mothers over 18 years old with at least one child (<18 years old) living in Cyprus. Results A total of 703 Cypriot mothers participated in the study. Most of the participants stated that they vaccined their children (97%) and the most popular source of information about vaccination was their pediatrician (90%). More than half of the participants (57%) have delayed their child/children vaccination with their pediatrician's suggestion being the main reason. 36% of mothers had low knowledge while the overall correct rate was 13.6% and the median (IQR) knowledge score was 11 (9-12). Having a medium knowledge about vaccination was associated with having a medium or high income, whilst high knowledge compared to low knowledge was associated with completed a higher education and having a high income. Our analysis showed that the correct knowledge by mothers with regards to vaccination increases the probability of vaccinating their children, following the local recommendations for vaccine dosages, and acquiring and trusting vaccination-related information from their children's pediatrician. Conclusion Our findings show that the majority of mothers in Cyprus had positives perceptions regarding childhood vaccination, as reflected with the high vaccination rate, however, some aspects of mothers' knowledge of vaccination need to be improved. Public health strategies to promote vaccination, education programs as well as improved communication tools between pediatricians and mothers need to be considered to achieve favorable vaccination attitudes and practices for all mothers in Cyprus.
Keywords: Vaccine hesitancy; Mothers; Educational Status; Vaccination of children